The impact of iceberg orders in limit order books - Stefan Frey; Patrik Sandås (University of Cologne, Centre for Financial Research (CFR), 2009)
We examine the impact of iceberg orders on the price and order flow dynamics in limit order books. Iceberg orders allow traders to simultaneously hide a large portion of their order size and signal their interest in trading to the market. We show that when the market learns about iceberg orders they tend to strongly attract market orders consistent with iceberg orders facilitating the search for latent liquidity. The greater the fraction of an iceberg order that is executed the smaller its price impact consistent with liquidity rather than informed trading. The presence of iceberg orders is associated with increased trading consistent with a positive liquidity externality, but the reduced order book transparency associated with iceberg orders also creates an adverse selection cost for limit orders that may partly offset any gains.
Keywords: G10; G14; 330; Hidden Liquidity; Iceberg Orders; Limit Order Markets; Transparency; Wertpapierhandel; Marktliquidität; Börsenumsatz; Mikrostrukturanalyse; Theorie